2014
DOI: 10.1166/jnn.2014.8681
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Evaluation of Poly(<I>ε</I>-Caprolactone) Nanocapsules Containing Triazine Herbicides

Abstract: The triazine class of herbicides includes the compounds ametryn, atrazine, and simazine, which are used to control weeds in plantations of crops such as maize, sorghum, and sugar cane. Despite their acceptance in agriculture, these herbicides can be dangerous to the environment, depending on their toxicity, the degree of contamination, and the duration of exposure. Controlled release systems are increasingly used to mitigate problems of toxicity and minimize environmental impacts, and can also increase herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 0 publications
1
31
1
Order By: Relevance
“…Herbicides encapsulated in the poly(ε-caprolactone) nanocapsules resulted in lower toxicity to the alga ( Pseudokirchneriella subcapitata ) and higher toxicity to the microcrustacean ( Daphnia similis ) as compared to the herbicides alone [122]. A list of nanoparticles used as herbicides against weeds in different vegetable crops is given in Table 3.…”
Section: Applications Of Nanotechnology In Precision Agriculturementioning
confidence: 99%
“…Herbicides encapsulated in the poly(ε-caprolactone) nanocapsules resulted in lower toxicity to the alga ( Pseudokirchneriella subcapitata ) and higher toxicity to the microcrustacean ( Daphnia similis ) as compared to the herbicides alone [122]. A list of nanoparticles used as herbicides against weeds in different vegetable crops is given in Table 3.…”
Section: Applications Of Nanotechnology In Precision Agriculturementioning
confidence: 99%
“…In vitro assays demonstrated the high efficiency of encapsulation of atrazine into the PCL nanocapsules and the high stability of the nanoformulation, as well as the controlled release of the herbicide from the nanocapsules (Grillo et al, 2012;Pereira et al, 2014). Toxicity assays conducted with the alga Pseudokirchneriella subcapitata, Allium cepa and human cells showed that atrazine-containing nanocapsules were less toxic to non-target organisms than the free herbicide (Grillo et al, 2012;Clemente et al, 2014;Pereira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoformulations of poly(ε-caprolactone) containing the herbicide atrazine were found to be effective for the control of the target Brassica sp and showed lower toxicity to the non-target organisms, eg, alga Pseudokirchneriella subcapitata, compared to the herbicide alone [92]. Encapsulated paraquat nanoformulations composed of chitosan and sodium tripolyphosphate, similarly as incorporation of paraquat [93] or clomazone to alginate/chitosan NPs [94] reduced environmental impact with simultaneous preservation of herbicidal effectiveness [95], and treatment with nanoparaquat resulted in less chromosome damage in Allium cepa [96].…”
Section: Nanoformulations Used For Plant Protection and Their Biologimentioning
confidence: 99%